The root signals in rhizospheric inter-organismal communications - Lyu, Dongmei; Smith, Donald L. (Frontiers in Plant Science, 2022)
Root exudates play a key role in mediating plant-plant and plant-rhizomicrobiome interactions, including regulating biochemical/physiological aspects of plant-associated microorganisms, to enhance host plant growth and resilience. Root exudates can act as signals reducing the competition from neighbouring plants and recruiting/choreographing a wide range of diverse rhizomicrobiome members to make the host-plant a good fit with its immediate environment. Root exudate production is a dynamic and key process but there is limited understanding of the metabolites or metabolic pathways involved in the inter-organismal communications facilitated by them. Given the well-known symbiotic relationships between plants and associated rhizomicrobiome members, adding root exudates to microbial isolation media may allow some of the large segment of rhizomicrobiome members not currently culturable to be grown in vitro. This would provide new insights regarding how root signals orchestrate associated microbes, will benefit agricultural production in the face of challenges posed by climate change, and help to sustainably provide food for a growing global human population.